Gelation of oil using combination of different free fatty acids. (July 2019) - Harris, Limor; Rosen-Kligvasser, Jasmine; Davidovich-Pinhas, Maya
Graphical abstract: Highlights: Oleogel system based on two different chain length fatty acids (FA) was formulated. Gelation process was altered based on the FA ratios. Antagonistic effect was observed in the gel hardness while combining the two FA. No co-crystallization of the two FA was observed. Abstract: Oil structuring system based on two different types of free fatty acids was examined using lauric acid (LA, 12:0) and behenic acid (BA, 22:0) as a model. The ability of different LA:BA ratios to structure canola oil was found to directly relate to the BA concentration, suggesting a stronger impact of the larger molecular architecture on the network formation. In addition, the mechanical performance of the LA:BA was hindered by the presence of LA thus producing softer gels compared to the simple addition of each component, suggesting an antagonistic effect between the two species. Similar trend was observed using various total structuring agent concentrations. Further rheology analysis revealed a thermo-gelation process controlled by BA crystallization in the LA:BA mixture emphasizing the role of BA in the network structure. This effect was also demonstrated in the network microstructure and oil binding capacity of LA:BA mixture, which resembled the characteristics of BA. Nano-structural analysis illustrated the presence of reflection peaks from both molecular species suggesting that separate nano-crystals were received. Thus, gel network was stabilized by the assembly of LA and BA nano-crystals. The current research demonstrate the first attempt to use combination of two different fatty acids to formulate oleogel matrix. The results clearly show that by introducing a mixture of fatty acids, and by choosing the fatty acids type and ratio, one could modify, in a controlled manner, the aforementioned properties, and thus fine-tune the oleogel performance for a specific application.